Tourist Perceptions About the Implementation of CHSE in Greater Bandung: A Preliminary Study - Harini Fajar Ningrum; Chandra Budhi Septyandi (Journal of Tourism Sustainability, 2021)
This research is based on the phenomenon of a shift in tourist behaviour during the Covid-19 pandemic. Cleanliness, Health, Safety, and Environment (CHSE) are the primary considerations for tourists when deciding to choose a tourist destination while on vacation, beating other aspects such as low prices. This study provides an initial picture of how tourists perceive the application of CHSE in a tourist destination. The method used in this research is descriptive quantitative through a survey using a questionnaire, then the results are tabulated into a frequency distribution table. The results of this study indicate that according to the perception of tourists who are dominated by the Millennials market segment, assessing that the application of CHSE in destinations around Bandung Raya is in the category of fair. Keywords: tourist perception, CHSE, Cleanliness, Health, Safety